Philippine laws, legislation and programs on dental waste management - Sunico, Michelle C. (The Journal of the Philippine Dental Association)
This article aims to highlight the pivotal role of the government in dental waste management. The current laws and legislations enacted will be enumerated. Available programs and possible projects to help implement these are also briefly discussed.